2018
DOI: 10.1097/aap.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Adductor Canal Block and Intrathecal Morphine to Analgesia and Functional Recovery After Total Knee Arthroplasty

Abstract: This study was registered at ClinicalTrials.gov, identifier NCT02411149.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Though the ACB results in less quadriceps weakness than FNB, it needs to be administered under ultrasound by an anaesthesiologist [19]. But, Biswas et al and Nader et al showed that ACB had better pain scores and lower opioid consumption than PAI alone [20,21]. Goytizolo et al also showed that combining PAI and ACB resulted in better pain scores [22].…”
Section: Discussionmentioning
confidence: 99%
“…Though the ACB results in less quadriceps weakness than FNB, it needs to be administered under ultrasound by an anaesthesiologist [19]. But, Biswas et al and Nader et al showed that ACB had better pain scores and lower opioid consumption than PAI alone [20,21]. Goytizolo et al also showed that combining PAI and ACB resulted in better pain scores [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cheah et al 30 conducted a retrospective study, which suggested that intrathecal morphine could still be considered for its benefits in the setting of modern multimodal analgesia for total joint arthroplasty. Biswas et al 31 recently conducted a randomized study to evaluate whether intrathecal morphine could offer any additional advantages in the context of multimodal analgesia. However, there has been no clinical study to investigate the role of intrathecal opioids in the setting of intravenous dexmedetomidine infusion and multimodal analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports, retrospective studies, cadaveric studies, non-English articles, review articles and meta-analyses were excluded (N = 69) (Included articles are listed in Supplemental Digital Content). The points of needle entry were grouped into 3 different regions ( Figures 4A and 4B): i) proximal blocks, 20,21 including block entry points that target the SFA after it has just beneath the medial border of the sartorius muscle, or the proximal-thigh approach by Meier et al involving the needle insertion at a location where the SFA is underneath the medial third of the sartorius muscle; ii) mid-thigh blocks, 3,10,20,22 including blocks performed at the midthigh level (between ASIS and base of patella), and the distal approach described Meier et al where the SFA lies underneath the middle third of sartorius; and iii) distal blocks, 11,22,23 including blocks performed at the dACB and other true AC blocks . Figure 4A shows the anatomical locations and Figure 4B shows the corresponding ultrasound image of the levels of these blocks.…”
Section: Discussionmentioning
confidence: 99%